ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF STATE CIVIL APPARATUS IN THE FIELD OF REGIONAL REVENUE MANAGEMENT OF THE REGIONAL REVENUE AGENCY OF NORTH SUMATERA PROVINCE - Nur Erdian Ritonga; Subhilhar; Heri Kusmanto (PT. Radja Intercontinental Publishing, 2025)
The state civil apparatus is one of the production factors, therefore it must be utilized optimally and productively. The goals of a government will not be realized without the active role of the state civil apparatus even though the tools owned by the company are so sophisticated and complete. Based on the Government Agency Performance Accountability Report, not all employees carry out their roles and functions properly. One of the problems in the Revenue Management Sector of the North Sumatra Provincial Revenue Agency is that many employees cannot keep up with the digitalization era, do not pay attention to the results of their work and the distribution of workload is uneven, so that social jealousy is created which makes competent and qualified ASN feel more burdened. This study aims to determine how much influence Individual Factors, Psychological Factors, and Organizational Factors have on the Performance of State Civil Apparatus in the Regional Revenue Management Sector of the North Sumatra Provincial Revenue Agency, totaling 50 people, samples were taken from the entire population or with saturated samples. The analysis technique uses multiple linear regression analysis, and the hypothesis test t-test, f-test, and determination test. The results of the study obtained an Fcount value of 25.533 with a significance of 0.000, while Ftable at a confidence interval of 95% or α = 0.05 is 2.723. By comparing the Fcount value with Ftable, then Fcount (25,533) is greater than Ftable (2,723). The decision is that H0 is rejected and Ha is accepted, meaning that simultaneously the variables of Individual Factors (X1), Psychological Factors (X2) and Organizational Factors (X3) have a very real (high significant) effect on the performance of the State Civil Apparatus in the Revenue Management Sector of the Regional Revenue Agency of North Sumatra Province. Meanwhile, the coefficient of determination obtained with a value of 69.0% of changes in the dependent variable (Performance of State Civil Apparatus in the Revenue Management Sector of the Regional Revenue Agency of North Sumatra Province) can be explained by changes in Individual Factors (X1), Psychological (X2) and Organization (X3). While the remaining 31% is explained by other factors outside the three variables as explained above such as work experience, work ability, benefits, and leadership style. The Head of the Regional Revenue Agency of North Sumatra Province is expected to prioritize improving the performance of state civil servants from punctuality, effectiveness and independence of workers and maintaining the need for supervision and interpersonal relationships of state civil servants.